Quality changes of minimally processed carabao mango (Mangifera indica Linn.) during refrigerated storage - Tabi, Huber P.; Acevedo, Teresita P. (2003)
The effect of refrigeration temperatures: -7°C, -2°C, 3°C and 8°C on the shelf life of minimally processed (MP) mango was determined. Quality of MP carabao mango was determined based on the sensory, physico-chemical and microbiological changes during storage. The best raw material quality of mango for processing was found to be the peak season premium carabao mangoes from Zambales at peel color index (PCI) number 5. Premium PCI number 6 mangoes from other provinces can also be used. The best temperature for MP mango storage was found to be 3°C. Shelf life at this temperature is 2 days as compared to less than 2 days for the other temperatures. Ice formation observed at -7°C and -2°C is detrimental to the texture of MP mango and early onset of browning discoloration and softening were observed at -7°C and early onset of browning discoloration and softening were observed at 8°C. Dipping MP mangoes in 30°Brix syrup extended the shelf life of minimally processed refrigerated (MPR) mango. Addition of preservatives further increased the beneficial effects of the syrup dips. Dipping mango cubes in 30°Brix syrup with 0.3% citric acid, 0.3% sodium erythorbate and 1% calcium chloride resulted to a shelf life of 7 days as compared to only 1 day for the control lot and less than 7 days for the other dips. Calcium chloride significantly improved the texture of MPR mangoes. Polyphenol oxidase activity was not affected by any of the treatments, and deterioration of carotenoids and ascorbic acid was not observed during MPR mango storage.
Thesis (M.S. Food Science)--University of the Philippines, Diliman.
Keywords: Mango -- Philippines -- Zambales -- Storage; Mango -- Philippines -- Zambales -- Cooling; Cold storage -- Philippines -- Zambales; Frozen fruit -- Philippines -- Zambales